Sanacija gozdov po katastrofah in Zavod za gozdove Slovenije - Oražem, Damjan (Gozdarski vestnik, 2017)
Along with climatic changes, natural disasters in forests are becoming ever more common. In such conditions, expectations by all stakeholders from the public forestry service have increased; on one hand, they are legitimate, but on the other hand they are often unrealistic. With regard to the ownership structure of forests, salvation success to a great extent actually depends on the public forestry service, whereby its activities in such situations can hardly be kept only within the tasks, determined by the Forest Act. After large disasters, forest salvation is an extensive and complex task, which should be addressed systematically, clearly considering priorities and following goals. Expectations by the public, forest owners, the media, and politics are, in addition to the expected complications, the very obstacle for the forestry service that sometimes arouses doubt about the correctness of the set goals both within this service as outside of it. Natural disasters in forests represent damage to many a person, from the owners on, but they also represent a spectrum of new opportunities; among them is also a consideration about changes in forest management or, respectively, forest ecosystems. Forest renovation also comprises questions about genetic material, tree species of the seedlings, cultivation, and, not at last, also about harmonization of fauna and flora components, which can block a successful forest regeneration. Forest salvations after natural disasters are certainly also a touchstone for the adequacy of public forestry service activities.
Keywords: forest regeneration; gozdovi; obnova gozdov; forest public service; javna gozdarska služba; natural disaster; Slovenia Forest Service; ujme; Zavod za gozdove Sovenije